Accompany unwanted pregnancies in education (Journal of Parents and Teachers, 2015)
This article describes the process of preventive action on sexual education and support in cases of unwanted pregnancies in the Colegio Sagrada Familia de Urgel in Madrid.
Keywords: Unwanted pregnancy; sex education; adolescence; sexual and reproductive rights; school support; education; educational guidance